A Clench-Fastened Boat in Kerala, India - Ralph K. Pedersen (The International Journal of Nautical Archaeology (2010) 39.1: 110-115, 2010)
In May 2003 the author observed a clench-fastened boat near Chertala, Kerala, India. The boat appears to indicate a vessel-type previously undocumented in the area. This article reports the observations made of the vessel and its pertinence to the boat-construction traditions of Kerala and the subcontinent.